(untitled) (African Journal of Biomedical Research, 2021)
A study to phenotypically characterize and determine the antibiogram of coagulase positive Staphylococci (CoPS) from the external surfaces of hospital cockroaches (Periplaneta americana ) was conducted using standard microbiological methods. Out of the 50 cockroaches collected from various hospital in Uyo, sixty-two percent (n = 31) had coagulase positive Staphylococci which consisted of Staphylococcus aureus (44.0 %; n = 22) and Staphylococcus intermedius (18.0 %; n = 9). The CoPS isolates showed 100% resistance to Penicillin, Tetracycline, Clindamycin and 80% sensitive to Amoxicillin-clavulanate. The CoPS showed multiple antibiotic resistances to ≥ 3 antibiotics, with 60 % exhibiting resistance to 6 antibiotics. Out of the 80 % (n = 31) of the multidrug resistant CoPS that were sensitive to Amoxicillin-clavulanate, none of them showed production of beta lactamase. The cockroaches borne multiple antibiotic resistant CoPS from their external surfaces and their contact can initiate contamination of patients’ food. Pest control measures in hospital are hereby recommended to minimize cockroach related infections.